Analisis HOTS Geometri Pada Keterampilan Berpikir Kritis dan Numerasi Ditinjau Gaya Belajar dan Gender - Diana, Nanang; Agustinasari, Agustinasari; Khatimah, Husnul; Ibnusaputra, M.; Adiansha, Adi Apriadi; Muslim, Muslim (Edumatica : Jurnal Pendidikan Matematika, 2025)
Critical thinking and numeracy skills are important competencies for students facing challenges of the 21st century and era of industrial revolution 5.0. In mathematics learning, especially geometry, using Higher Order Thinking Skills (HOTS) questions is a strategic approach to developing these abilities. This study analyzes students' critical thinking and numeracy skills through HOTS geometry questions, reviewed by learning styles and gender. The research uses a quantitative descriptive method with a purposive sample of 26 VIII-grade students at SMP Negeri 1 Kota Bima. Results indicate that male students with visual learning styles achieved the highest scores in both skills. Visual learning styles were more effective in supporting numeracy skills, whereas auditory and kinesthetic styles supported critical thinking more effectively. ANOVA tests revealed significant differences in numeracy skills on the "making decisions" indicator by learning style (Sig. 0.047) and gender (Sig. 0.0291), and in critical thinking skills on the "inference" indicator by gender (Sig. 0.0265). In conclusion, learning styles and gender influence critical thinking and numeracy, with learning style having the more pronounced effect. Future research is needed to train students in answering HOTS questions to enhance both skills.